2019
DOI: 10.1111/1556-4029.14009
|View full text |Cite
|
Sign up to set email alerts
|

An Experiment to Characterize the Decomposer Community Associated with Carcasses (Sus scrofa domesticus) on Oahu, Hawaii

Abstract: Pig (Sus scrofa domesticus) carcasses were decomposed on the soil surface of a terrestrial habitat on the island of Oahu, Hawaii to begin characterizing the decomposer community. Results showed that carcasses can decompose rapidly on Oahu, primarily due to the activity of fly larvae, with ~80% of mass lost by 8 days (~220 ADD) postmortem. Scavenging was conducted exclusively by the small Indian mongoose (Herpestes javanicus), first feeding on larvae then feeding on the remains. Carcasses were habitats of warm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…Early studies have shown that larval masses on pig carcasses act as oxygen-reducing environments with raised temperatures and generally neutral pHs, and microbial communities that shift across the stages of decomposition (Chun et al, 2015). Dibner et al (2019) showed similar results, and noted that later in decomposition anaerobic bacteria dominated the microbial communities. Junkins et al (2019) showed that the microbe community structure was heavily influenced by oxidation-reduction potential, which, in turn, was altered by the maggot mass.…”
Section: Hawai'imentioning
confidence: 85%
See 1 more Smart Citation
“…Early studies have shown that larval masses on pig carcasses act as oxygen-reducing environments with raised temperatures and generally neutral pHs, and microbial communities that shift across the stages of decomposition (Chun et al, 2015). Dibner et al (2019) showed similar results, and noted that later in decomposition anaerobic bacteria dominated the microbial communities. Junkins et al (2019) showed that the microbe community structure was heavily influenced by oxidation-reduction potential, which, in turn, was altered by the maggot mass.…”
Section: Hawai'imentioning
confidence: 85%
“…While forensic entomologists in Hawai'i have established a strong baseline of work to reference in pursuit of more advanced topics like assessing microbial communities (Chun et al, 2015; Dibner et al, 2019) and diagnosing novel morphological characteristics to aid in identification (Flores et al, 2016), it is important for baseline decomposition studies to continue to be replicated in Hawai'i. Continued replication of these projects is key in helping to detect new species arrivals and variations in carrion‐associated insect communities across the state, and to continue building an even more robust baseline of knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…The Steadman et al [25] study, for the first time, provided solid evidence that PMI estimates are significantly impacted when using previously established models where human cadavers are concernedhuman PMI estimates are overestimated and pig PMI estimates are underestimated when compared to estimates calculated from studies where scavengers were excluded. It should be noted that terrestrial vertebrate scavenging activity is not restricted to raccoons and mongooses; the literature reports such species as coyotes, bears, opossum, turkey vultures, domesticated dogs, red fox and carrion crows, among others, having taphonomic impacts on human and proxy remains [54][55][56][57][58][59][60][61][62][63]. This list is expected to grow as human settlements encroach more and more onto natural habitats and animals become more synanthropic.…”
Section: Forensic Realismmentioning
confidence: 99%
“…Dibner et al [24] report on an experiment to characterize the scavenger community on the Hawaiian island Oahu. The authors observed that the Indian mongoose (Herpestes javanicus), a species not native to the Hawaiian islands, was the sole vertebrate scavenger of the carcasses.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, the mongooses appeared to have been attracted to the larvae colonizing the remains before transitioning to scavenging the decomposing flesh. Also described in this paper are the species of bacteria active on the remains, which provides a more holistic view of a decomposer community [24].…”
Section: Introductionmentioning
confidence: 99%